1998
DOI: 10.1007/bf02464807
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow dynamics in different layers of the somatosensory region of the cerebral cortex on the rat during mechanical stimulation of the vibrissae

Abstract: The present work reports studies of the quantitative spatial and temporal characteristics of changes in local blood flow in different layers of the somatosensory cortex of rats during adequate mechanical stimulation of the vibrissae. Studies were performed using 34 Wistar rats. Skull trepanning was performed under urethane (1 g/kg) anesthesia. Television-guided microscopy was used to introduce a set of three platinum electrodes (100 microns in diameter, with tip diameters of 30-40 microns) into the somatosenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…The CBF increases were much smaller in the upper 0‐250 μm than in deeper cortical layers. This is consistent with results using mechanical whisker stimulation and the hydrogen clearance method (Moskalenko et al 1996, 1998), and a recent study using autoradiographic techniques (Gerrits et al 2000). The vascularity of the cortex may influence the flow signal as the highest capillary density is found in layer IV, corresponding to the maximal synaptic input (Patel, 1983).…”
Section: Discussionsupporting
confidence: 92%
“…The CBF increases were much smaller in the upper 0‐250 μm than in deeper cortical layers. This is consistent with results using mechanical whisker stimulation and the hydrogen clearance method (Moskalenko et al 1996, 1998), and a recent study using autoradiographic techniques (Gerrits et al 2000). The vascularity of the cortex may influence the flow signal as the highest capillary density is found in layer IV, corresponding to the maximal synaptic input (Patel, 1983).…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that hemodynamic regulation is heterogeneous and that functionally induced microvascular changes can occur at small spatial scales, i.e., at the level of columns and layers (Chaigneau et al, 2003; Erinjeri and Woolsey, 2002). Laminar differences in blood volume and flow have been observed in baseline conditions as well as after stimulation, showing that blood flow regulation differs between layers and between superficial vessels and parenchyma (Choi et al, 2010; Moskalenko et al, 1998; Zaharchuk et al, 1999). Baseline blood flow and vascularization are highest in the center of the cortex (Duvernoy et al, 1981; Gerrits et al, 2000; Moskalenko et al, 1998; Weber et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Laminar differences in blood volume and flow have been observed in baseline conditions as well as after stimulation, showing that blood flow regulation differs between layers and between superficial vessels and parenchyma (Choi et al, 2010; Moskalenko et al, 1998; Zaharchuk et al, 1999). Baseline blood flow and vascularization are highest in the center of the cortex (Duvernoy et al, 1981; Gerrits et al, 2000; Moskalenko et al, 1998; Weber et al, 2008). Upon stimulation, blood flow increases throughout the cortex, with the highest CBF increases in the middle layers (Moskalenko et al, 1998; Norup Nielsen and Lauritzen, 2001; Takano et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have proposed and demonstrated the use of dynamic ADC contrast to focus on the small vessel networks closely tied to the true neuronal activities (Ngai et al, 1995;Malonek and Grinvald, 1996;Moskalenko et al, 1998;Sheth et al, 2003), using multiple diffusion-weighting conditions. Diffusion-weighting selectively attenuates MR signals from proton pools undergoing a random-walk diffusion process (Torrey, 1956).…”
Section: A Basicmentioning
confidence: 99%